THE REVIEW OF SNACK BAR FROM CHIA - MOCAF AS AN ANTIDIABETIC FOOD - Saskia Revinka Maharani; Vega Yoesepa Pamela; Septariawulan Kusumasari (Food ScienTech Journal, 2021)
Due to the high activity, plus the problem of communicable and non-communicable diseases such as diabetes, there is an increasing public awareness of the need for food that is practical and has an effect on improving body health. the Snack bar is convenient food that has complete nutritional content. Some food ingredients that can be used as raw material for making anti-diabetic snack bars are chia seeds (Salvia hispanica L) and cassava (Manihot esculenta). Based on existing research, chia seed and modified cassava flour (mocaf) have a hypoglycemic function which is closely related to reducing blood sugar levels so that it can reduce the risk of diabetes. Chia seeds are well known for their high oil content, are rich in polyunsaturated fatty acids, especially omega- 3 and omega-6 fatty acids, and are high in protein and fiber which increase their potential as a functional food product. The content mocaf flour in 100 grams are protein 1.2%, fat 0.4%, and 3.4% fiber. Chia seed flour has been shown to increase AMPK expression, while mocaf can increase insulin sensitivity in type 2 diabetes mellitus.